Metode Netnografi Menguliti Narasi Banjir Sumatera: Alam Dikambinghitamkan, Korporasi Disalahkan, Pemerintah ke Mana? - Thamira Ahsilla Barkah; Soca Berlianto; Eka Permana; Ovalia Rukmana (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Recurrent flooding in Sumatra has triggered intense debate on social media regarding its underlying causes and the attribution of responsibility. While previous disaster studies in Indonesia have largely emphasized technical and physical dimensions, limited attention has been given to how public discourse frames flood causality in digital spaces. This study aims to examine how the causes of flooding in Sumatra are constructed in social media discourse and to identify which actors are most prominently associated with responsibility. Employing a qualitative multi-platform netnographic approach, this research analyzes user-generated comments from Facebook, YouTube, and TikTok collected during the first month following major flood events. Data were examined using NVivo 15 through word frequency analysis, word cloud visualization, and hierarchical mapping to identify dominant themes and framing patterns. The findings reveal that public discourse predominantly frames flooding as a natural and moral phenomenon, emphasizing environmental factors and religious interpretations. Although references to government accountability and corporate activities such as deforestation and extractive industries are present, they appear less frequently and in fragmented forms. These results suggest that social media discourse tends to depoliticize flood risk by foregrounding natural explanations, while structural and governance-related factors remain marginal. This study contributes to disaster communication scholarship by highlighting the discursive production of disaster risk in digitally mediated public arenas.